Perkembangan Library Cafe dalam Mendorong Produktivitas Pemustaka di Indonesia: Studi Literatur - Aliwijaya, Araf (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
Library cafes are one of the developments currently being carried out in several libraries in Indonesia. However, there are views that agree and disagree with the concept of cafes in libraries. This research aims to identify and analyze the development of library cafes in Indonesia. The development of the library cafe application is discussed based on various available literature. This research uses a qualitative approach with a research method, namely literature study. Data was obtained from relevant literature references such as books, journals, activity reports, and websites relevant to the problem theme. The analysis process is carried out on the data obtained, namely by making data reduction, data presentation, data reduction, and drawing conclusions. There are several differences in how library cafes are called, such as library cafe, libri cafe, library cafe or library cafe, literacy cafe, and library cafe. The library cafe has many programs such as book reviews, discussions, music concerts and others. The aim of developing a library cafe is to improve the quality of the library and the number of user visits. The advantages and disadvantages contained in the library cafe can be used as a basis for improving and improving library services.